A patient with a history of syncope experiencing cardiac arrest after brachial plexus block - Ni, Liya (Journal of the Pakistan Medical Association, 2026)
A 65-year-old male with a history of hypertension and diabetes, experienced syncope and cardiac arrest during shoulder arthroscopy after receiving a brachial plexus block. The patient, who was sedated with dexmedetomidine, developed bradycardia after being positioned in the beach chair position, which lead to cardiac arrest. Prompt cardiopulmonary resuscitation restored the patient’s heart rate and consciousness. This report discusses the possible causes, including the vasovagal reflex, dexmedetomidine effects, and Bezold-Jarisch reflex, and proposes preventive measures. Recognising high-risk individuals and implementing preventive strategies is crucial. Keywords: Brachial plexus block, Bezold-Jarisch reflex, cardiac arrest, syncope.